Influence of Water Temperature and Flow Velocity on Locomotion Behavior in Tropical Commercially Important Sea Cucumber Stichopus monotuberculatus - Chen, Mengling; Sun, Shuo; Xu, Qiang; Gao, Fei; Wang, Haiqing; Wang, Aimin (Frontiers in Marine Science, 2022)
Sea cucumber Stichopus monotuberculatus is one species of tropical sea cucumbers with high recognition and economic value. While advances have been made in the nursery rearing of the sea cucumber, influence of environmental factors on its locomotion behavior remains less understood, which restricts the establishment of mariculture technologies. In the present study, locomotion behavior of S. monotuberculatus under different temperatures and flow velocities were examined through controlled simulation experiments. Results showed that the creeping activities were obviously affected by temperature, and the most active movement and feeding behavior were recorded at relatively high temperatures. Diurnal variation of locomotion and feeding activities indicated that S. monotuberculatus displayed an evident nocturnal activity pattern, being the most active at night, exhibiting intermediate activity at dusk, and minimal activity during the daytime. The movement velocity decreased with the increasing flow speed and was only 1.65 ± 1.35cm·min-1 in the highest flow rate group (20.8 ± 3.4cm/s). Moreover, the sea cucumber S. monotuberculatus displayed positive rheotaxis behavior of moving downstream at all flow velocities. Overall, the sea cucumber S. monotuberculatus exhibited high locomotor and feeding activities at night of relatively high temperature, and its favoured flow regime was downstream and low water velocity area. These findings may assist the sea ranching and aquaculture development of the tropical commercial sea cucumber species.